THE CORECT BODY MECHANIC PRINCIPLE AND LOW BACK PAIN IN THE THIRD TRIMESTER PREGNANT WOMEN - Hany Kharisma Dewi; Sugeng Maryanto; Dewi Puspita; Agi Yulia Riadini (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Low back pain is one of the inconveniences in pregnant women which normally will increase along with the increasing of gestational age because this pain is caused by the shift of the center of gravity in a woman and her posture. The good body mechanic is needed to establish the safe and comfortable daily activities during pregnancy and to prevent and reduce back pain. Aims: This study aimed to analyze the correct body mechanic principle with low back pain complaints in the third trimester pregnant women at the work region of Kambangan health center Sub-district Lebaksiu Tegal Regency. Method: This study used cross-sectional design. The population used in this research is pregnant women of the third trimester in the working area of Kambangan health center,Lebaksiu Sub District Tegal, population in this study as much 36 third trimester pregnant women and 24 respondents as sample. Result: There were 58.3% of the respondents who had good body mechanic, while 45.8% of the respondents experienced back pain. The bivariate analysis indicated that there was a correlation between body mechanic and back pain in the third trimester pregnant women with the p-value of 0.011. Conclusion: The results of this study indicate that the correct body mechanic principle can prevent low back pain in the third trimester pregnant women at Kambangan Health Center Lebaksiu Sub-district Tegal Regency and to reduce low back pain in pregnant women, midwives need to provide health education about the correct body mechanic during pregnancy to prevent low back pain.